Aligning Orifice of the Renal Artery with Fish-Mouth FIXation Technique During Endovascular Aortic Aneurysm Repair for Hostile Neck Anatomy. (April 2023) - Domoto, Satoru; Azuma, Takashi; Hayakawa, Minako; Yamagata, Akiko; Isomura, Shogo; Niinami, Hiroshi
Background: As the success of endovascular aortic aneurysm repair (EVAR) depends on sufficient proximal fixation of the endograft to the aortic wall, the proximal hostile neck anatomy (HNA) is the major potential treatment-limiting factor in EVAR. The Aorfix endovascular stent graft was designed to operate on highly angulated aortic necks. The Aligning Orifice of the Renal artery with fish-mouth FIXation (AORFIX) technique uniquely and accurately aligns the trough part of the proximal stent end with the orifice of the lower renal artery and is used to optimize the proximal fish-mouth design for maximum proximal seal use. Herein, we aimed to evaluate the usefulness of the AORFIX technique for EVAR in patients with HNA.Methods: Eighty-one consecutive patients who underwent EVAR with the AORFIX technique (+AORFIX technique group, n = 16) and without (standard group, n = 65) were evaluated. The HNA was defined as any of the following: neck angulation ≥60°, neck length ≤15 mm, or neck thrombus or calcification ≥50% of the circumference and conical neck.Results: Each HNA criterion was similar between the two groups. However, the average number of HNA criteria was significantly higher in the +AORFIX technique group (1.9 ± .2 vs. 1.3 ± .1; P < .01). The two groups showed 100% procedural success. The concurrent renal angioplasty and stenting rates (88% vs. 4.6%; P < .01) were significantly higher in the +AORFIX technique group. There were no 30-day deaths in either group and no in-hospital device-related events in the +AORFIX technique group. The median follow-up period was 39 months, and there was no significant between-group difference in freedom from reintervention rate (+AORFIX group vs. standard group, 100% vs. 91.0%; P = .327).Conclusion: EVAR using the AORFIX technique might be useful even in patients with more complex HNA.